A colorimetric/luminescence sensor for detecting MeCN in water: Towards direct detection of dissolved organic contaminants - Norton, Amie E.; Abdolmaleki, Mahmood Karimi; Ringo, Jessica M.; Shingade, Vikas M.; Cashen, Christina; Sharma, Malvika; Connick, William B.; Chatterjee, Sayandev (Sensors and actuators. B, Chemical, 2021)
Highlights •Molecular recognition of organic contaminants in water by a linear Pt(II) complex.•Highly targeted luminescence and colorimetric response of the complex to acetonitrile in water.•The proportional increase of luminescence intensity of an MMLCT band with MeCN concentration allows for quantification as well. [Display omitted] To address the need for a field-deployable in-situ technique for the accurate and reliable detection of organic contaminants in water, this work reports a new chemical sensing approach for the detection of aqueous MeCN. The approach relies on the reversible colorimetric/luminescent change in a transition metal complex. In this approach, a square planar platinum salt [Pt(tpy)Cl](PF6) (tpy = 2,2′:6′,2″-terpyridine) demonstrated a reversible color change from yellow to red as well as a red shift in emission intensity upon exposure to aqueous MeCN. This observed spectroscopic change was induced by the incorporation of MeCN molecules withing the crystal lattice of the platinum salt, that resulted in an enhancement in the intermolecular Pt•••Pt interactions, which correlatively altered the electronic structure. The spectroscopic response was highly selective and quantitative for aqueous MeCN. This work illustrates a new technique for the rapid, selective, sensitive detection of aqueous MeCN, while also providing a general strategy for the detection of other small molecule contaminants.